PROSPECTS OF BIOMETRICS IN INFORMATION SECURITY - Juraev, Dilshodbek Makhsutali ugli; Pirnazarov, Ulugbek Umataliyevich (Educational Research in Universal Sciences, 2023)
The article discusses the issue of using biometric systems in information systems from the point of view of ensuring information security. Risks that may affect safety and ways to minimize them are highlighted.